PENGETAHUAN GIZI, AKTIVITAS FISIK, DAN TINGKAT KECUKUPAN GIZI AKTIVIS BADAN EKSEKUTIF MAHASISWA (BEM) IPB - Susi Nurohmi; Leily Amalia (Food and Nutrition Society of Indonesia, 2012)
The study was aimed to analyze nutrition knowledge, physical activity, and nutrient adequacy level among Excutive Board Students of Bogor Agriculture University (BEM-IPB). The study was conducted since February until May 2012 in Campus of IPB Dramaga, Bogor. The subjects were 86 students, selected purposively from every areas of BEM faculties. The data consisted of individual characteristics, nutrition knowledge, physical activity, and daily food consumption. Data of food consumption was collected by 2x24 recall method at weekend and class day. In average, nutritional status of subjects was categorized as normal (BMI 21.7±2.9 kg/m2). Subjects nutrition knowledge mostly was moderate (79.1%). Physical activity of subjects in general was light (PAL=1.64). This implied to amount of estimated energy requirement which is lower than amount of recommended energy intake for Indonesian people, i.e 2,349 kcal vs 2,550 kcal (for men) and 1,851 kcal vs 1,900 kcal (for women). In general, the means of nutrients adequacy level were adequate, energy and protein (90—110%RDA), and micronutrients of vitamin A, vitamin B, and iron (>77%RDA). However, adequacy level of vitamin C and calsium was still deficient (<77%RDA). Based on %RDA category, there was a different trend in subject distribution between macro dan micronutrients. %RDA of energy and protein were mostly categorized as adequate (40.0% and 33.0% respectively). However, in case of micronutrient, subject categorized as deficient was larger than adequate, especially on vitamin C (77.0% vs 23.0%), calsium (66.0% vs 34%) and iron (55.0% vs 45.0%).